2019
DOI: 10.1039/c8me00087e
|View full text |Cite
|
Sign up to set email alerts
|

Ion specific, odd–even glass transition temperatures and conductivities in precise network polymerized ionic liquids

Abstract: Network architectures reveal odd–even effects in existing PIL systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 75 publications
1
34
1
Order By: Relevance
“…1c). The increase in crosslink density is expected to lead to a monotonic increase in T g , 49 but a reproducible non-monotonic trend is observed. This is correlated with the appearance of crystallization during quenching and cold crystallization on heating in the C 10 and C 12 networks (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1c). The increase in crosslink density is expected to lead to a monotonic increase in T g , 49 but a reproducible non-monotonic trend is observed. This is correlated with the appearance of crystallization during quenching and cold crystallization on heating in the C 10 and C 12 networks (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work from our group on permanent networks showed that odd-even effects can emerge in amorphous materials when the linkers are precise, and T g jumps up and down as the carbon number systematically increases from 4 to 12. 49 Winey and coworkers 50 have also shown the importance of precision spacing of ionic groups along a polyethylene backone which can crystallize and form favorable structures for proton conduction. In the context of vitrimers, an understanding of how precise spacing of dynamic bonds impacts the macroscopic rheology is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most often used basic structures (although many other have been reported [ 31 , 32 , 49 , 50 , 51 , 52 ]) is the imidazolium ring with the TFSI counter ion, resulting in cationic-type polymers. In these polymers, the basic cationic units can be positioned in the polymer backbone [ 53 ], as side chains either in linear [ 36 , 37 ] or in crosslinked polymers [ 54 , 55 , 56 , 57 ], together with anions in the side chain (zwitterionic type), in alternating copolymers or blockwise [ 21 , 32 , 46 , 58 ] accompanied by anionic side chains [ 31 , 54 ], and in the arms of star-shaped polymers. TFSI, as a counterion for cationic sites, is particularly preferred owing to the high van der Waals volume and week binding affinity to Li + cations [ 36 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…High T g PILs have greater mechanical stability but lower ionic conductivity due to lower segmental mobility. [57] Many groups have noted the important roles of polarity, ion concentration, polymer morphology, and segmental dynamics on conductivity in linear single-ion conducting systems.. [21,[57][58][59][60] Prior works on single anion conducting network polymers have investigated the roles of network versus linear architecture, [35] precise length of carbon spacers between network junctions, [61] crosslinking density, [16,62,63] ionic interactions, [55,63,64] and ion concentration [55] on ion transport through changes in T g and mechanical properties. However, there is still a need for systematic studies of Li + single-ion conducting networks with controlled architecture, charge density, and mechanical properties to understand how performance is related to molecular structure.…”
Section: Introductionmentioning
confidence: 99%